Growth of binder-free highly efficient supercapacitors electrode materials based on nickel sulfide nanostructures anchored on hierarchical nickel foam - Misbah Yousaf; A. Farid; A. Rasheed; A. Raza; M. Ahsan Ali; I.A. Khan (Journal of Saudi Chemical Society, 2024)
The synthesis of highly efficient supercapacitor electrode materials (E-Ms) based on innovative nanostructured nickel sulfide is necessarily to reduce the energy crises. Herein, the highly efficient E-Ms based on nickel sulfide nanostructures are synthesized by a simple, home-made and cost-effective chemical vapor deposition technique. The values of structural parameters like peak intensity (292.63–359.58) and crystallite size (36.78–39.06 nm) of nickel sulfide E-Ms are increased while the values of dislocation density (7.46–6.55 nm−2) are decreased with increasing weight of sulfur powder. The microstructural features of nickel sulfide E-Ms is changed from irregular nano-sheets to nanoclusters with increasing weight of sulfur powder. The values of electrochemical parameters like specific capacitance (calculated from cyclic voltammetry and galvanometric charge–discharge profiles) of nanostructured nickel sulfide E-Ms are ranged from 5139 to 2804 F/g at 1 mVs−1 and 3079–1246 at 12 A/g respectively. The values of energy density are found to 52–28 Wh/kg (at power density = 2100 W/kg) are decreased to 21–7 Wh/kg (at power density = 6144 W/kg) with increasing weight of sulfur power (50–100 mg) respectively. The excellent cyclic stability and capacity retention (99–93 %) of nanostructured nickel sulfide E-Ms are observed. The appearance of negligibly small semicircle in electrochemical impedance analysis (in high frequency region) and the small equivalent series resistance (0.33–0.38 Ω) confirm the nanostructured nickel sulfide E-Ms can be used as highly efficient pseudocapacitor with 74 % capacitive nature. The Dunn’s Model simulation also predicts that the capacitive contribution of nanostructured nickel sulfide E-Ms is increased up to 74 % with increasing scan rates and thus can be used as highly efficient pseudocapacitor in portable energy storage devices. Results demonstrate that the highly electrochemical efficient pseudocapacitor based on nanostructures nickel sulfide can be synthesized by the said simple technique.